Gentrifikasi Canggu: Perspektif Penduduk Lokal Terhadap Overtourism - Ranya Mahaputri Hartono; Ni Kadek Winda Yanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Tourism development in Canggu has increased significantly over the past decade. The transformation of an agrarian area into a modern tourist hub has given rise to the phenomena of overtourism, increased environmental pressures, and gentrification, driving social, economic, and cultural change. This study aims to understand how local communities construct meaning around these changes, how they adapt, and how socio-cultural identities are redefined in a rapidly changing environment. This study uses a descriptive qualitative approach using in-depth interviews, non-participatory observation, and documentation. Data were analyzed using the Miles & Huberman model through data reduction, data presentation, and conclusion drawing. The results show three main findings. First, overtourism is understood ambivalently: residents enjoy economic benefits but experience pressures such as traffic jams, noise pollution, and diminished social interaction. Second, residents adapt through job diversification, room rentals, and land sales, despite the resulting inequality and the risk of losing living space. Third, gentrification causes a shift in cultural identity, ranging from the commercialization of traditional ceremonies to a decline in communal solidarity. This research emphasizes the importance of participatory communication in tourism management so that local communities are not marginalized from their social and economic space.